Text and Context: A study of the Proverbs and Folksongs of Akpor kingdom, Rivers State, Nigeria (Eurasian Journal of Humanities and Social Sciences, 2023)
Folklores are forms of oral literature that are very important to the Akpor people as they serve as ways through which the Akpor traditions, cultures and customs are made known to the people. Presently, the use of proverbs and folksongs have been greatly reduced due to the influence of western culture as people hardly engage in these cultural practices from whence these forms of oral literature are elicited. The objectives of this study is to identify the various types of folksongs and proverbs existing in Akpor kingdom, analyse these songs and proverbs and examine the roles context play in deciphering the meaning of these oral forms of literature. The major source of data collection for this study is oral interviews, particularly unstructured interviews. The study adopts the use or contextual theory of meaning for its framework. The findings show that context influences, but does not determine meaning. In other words, proverbs or folksongs used in similar contexts could have distinct meanings, depending on the societal needs they are meant to address. Folksongs can be modified by singers to suit their personal taste and through these forms of oral literature, abstract elements such as ideas, emotions and values are represented. This study also identified that the active participants of these forms of oral literature are mostly elderly men and women. Children of the present generation barely speak their language and therefore rarely participate in these cultural activities where these forms of oral literature are elicited. This is because they believe that they are fetish. It therefore recommends that the cultural activities from where these oral forms of literature can be elicited should be restored and modified to meet the needs and acceptance of the present generation rather than neglecting them. This is because if these cultures are not being practised, the language imbibed in that domain gradually dies off.